An activin receptor IIA ligand trap promotes erythropoiesis resulting in a rapid induction of red blood cells and haemoglobin. (18th March 2014) - Carrancio, Soraya; Markovics, Jennifer; Wong, Piu; Leisten, Jim; Castiglioni, Paola; Groza, Matthew C.; Raymon, Heather K.; Heise, Carla; Daniel, Tom; Chopra, Rajesh; Sung, Victoria
Summary Sotatercept (ACE‐011), a recombinant human fusion protein containing the extracellular domain of the human Activin receptor IIA, binds to and inhibits activin and other members of the transforming growth factor ‐β (TGF‐β) superfamily. Administration of sotatercept led to a rapid and sustained increase in red blood cell (RBC) count and haemoglobin (Hb) in healthy volunteers (phase I clinical trials), but the mechanism is not fully understood. Mice treated with RAP‐011 (murine ortholog of ACE‐011) respond with a rapid (within 24 h) increase in haematocrit, Hb, and RBC count. These effects are accompanied by an equally rapid stimulation of late‐stage erythroid precursors in the bone marrow (BM). RAP‐011 also induces a significant increase in erythroid burst‐forming units and erythropoietin, which could contribute to additional, sustained effects on RBC production. Further in vitro co‐culture studies demonstrate that BM accessory cells are required for RAP‐011 effects. To better understand which TGF‐β family ligand(s) mediate RAP‐011 effects, we evaluated the impact of several of these ligands on erythroid differentiation. Our data suggest that RAP‐011 may act to rescue growth differentiation factor 11/Activin A‐induced inhibition of late‐stage erythropoiesis. These data define the mechanism of action of a novel agent that regulates RBC differentiation and provide the rationale to develop sotatercept for the treatment of anaemia and ineffective erythropoiesis.